PERFORMANCE EVALUATION OF WCDMA RADIO OVER FIBER SYSTEM (WCDMA-ROF) - ARIEFIANTO WIBOWO (NIM 23206046), TODY
The demand for broadband services has driven research on millimeter wave communications. Especially when we deal with issue of spectrum availability, and the size of communication devices. In the other hand, upcoming wireless networks are expected to do dynamic allocation to cope with traffic variations. Radio Over Fiber is a technique to transmit radio signal over optical fiber in wireless infrastructure network that give low-cost, practical usage, and flexibility system configuration advantage. However, ROF system has weaknesses from laser diode nonlinearity and fiber optic chromatic dispersion. Therefore, the performance of WCDMA system which is integrated with radio over fiber system is evaluated in this research. It will be analyzed and compared performance of WCDMA system in eight scheme, which are influence of different fiber length, influence of different lambda, influence of different data rate, influence of user amount, influence of channel coding, influence of interleaver, influence of different coding rate, and influence of nonlinearity. Channel Model of radio over fiber which is used in this simulation consist of Relative Intensity Noise, laser diode nonlinearity, and fiber optic dispersion chromatic. The simulation is done within Matlab 7.0 environment. The results of simulation show commonly WCDMA system integrated with radio over fiber system have a good performance.